(untitled) (Iraqi Journal of Science, 2023)
In this paper, the effects of prey’s fear on the dynamics of the prey, predator, and scavenger system incorporating a prey refuge with the linear type of functional response were studied theoretically as well as numerically approach. The local and global stabilities of all possible equilibrium points are investigated. The persistence conditions of the model are established. the local bifurcation analysis around the equilibrium points, as well as the Hopf bifurcation near the positive equilibrium point, are discussed and analyzed. Finally, numerical simulations are carried out, and the obtained trajectories are drowned using the application of Matlab version (6) to explain our found analytical result.